Greater Mekong Subregion health cooperation strategy 2019-2023. (Metro Manila, Philippines Asian Development Bank, 2019)
This publication provides a framework to guide the six member countries of the Greater Mekong Subregion (GMS) on collaboration to tackle priority health issues.
Keywords: Health care reform -- Asia; Health services accessibility -- Developing countries; Electronic books